Endogamous marriage and the prevalence of hemoglobin E in ethnic groups of northern Thailand - Praphat Ruengthanoo (2018)
© 2017 Hainan Medical University Objective To investigate the impact of the endogamous marriage culture on the prevalence of the hemoglobin E (HbE) recessive variant. Methods The prevalence of the hemoglobin E (HbE) recessive variant was determined by dot-blot hybridization in 4 endogamous villages (1 Mlabri and 3 Htin ethnic groups) in comparison with 9 other nearby non-endogamous populations. Results Although the overall HbE prevalence in the population studied (8.44%, 33/391) was not significantly different from that of the general southeast Asian population, a high prevalence and individuals with homozygous HbE were observed in two villages, the Mlabri from Wiang Sa district and the Htin from Thung Chang district of Nan province (26.3% and 26.9%, respectively). The low HbE allelic frequency noticed in some endogamous populations suggests that not only endogamy but also other evolutionary forces, such as founder effect and HbE/β-thalassemia negative selection may have an effect on the distribution of the HbE trait. Conclusion Our study strongly documents that cultural impact has to be considered in the extensive prevalence studies for genetic disorders in the ethnic groups of northern Thailand.